Representations of adult women who have experienced 'absent' fathers: a thematic analysis of True Love magazine - Moola, Lubayna Codelia (Rhodes University, Faculty of Humanities, Department of Psychology)
This study explored how adult women who have experienced father 'absence' are represented in True Love magazine, a popular South African women's magazine targeting black women readers. The study examined nineteen articles published between 2016 and 2021 in True Love, featuring black women's stories and clinical psychologists, which mentioned 'absent' fathers. Through the lenses of psychoanalytic, traditional African cultural, and feminist theoretical frameworks and their key concepts, the articles were examined in relation to how the effects on the adult women of complicated relationships with their fathers while they were growing up, were represented. The selected articles were analysed using Braun and Clarke's reflexive thematic analysis, and representational themes were identified guided by theoretical frameworks and familiarity with the scholarly literature on father 'absence' in South Africa. A wide range of childhood and young adult experiences of father-daughter relationships, and household circumstances, appeared alongside the strong maternal networks which supported these girls and women. Representations and themes of clinical psychologists involved Freudian psychoanalytic frameworks to describe the damaging psychological implications of 'absent' fathers, particularly affecting adult women's capacities to form trusting intimate relationships with men. The adult women's stories "“ largely successful businesswomen and/or celebrities in the arts, as represented by True Love feature writers and editors "“ presented themes of what the women had learnt from their mothers, and how they had overcome difficulties and obstacles. These themes included representations of resilience, and of being 'survivors', informed by empowerments from a feminist theoretical framework. These themes also represented the women as working psychotherapeutically to manage their past experiences and psychological distress, to transform their retriggering in adult heterosexual relationships, and to pursue healing and self-actualisation. These representations and themes are argued to have inspirational and motivating implications for girls and women in contemporary South Africa. They generate alternate stories about the longer-term effects and outcomes of father 'absence', rather than the prominent 'victim' stories in media and scholarly literature of young women doomed to suffer poor relationships and depression forever.
Keywords: Absentee fathers -- South Africa; Fathers and daughters -- South Africa; Fathers and daughters in literature -- South Africa; Mass media and families -- South Africa; Mass media and women -- South Africa; Families Psychological aspects; Self-actualization (Psychology) in women -- South Africa; Thematic analysis; True Love magazine